Heat transfer coefficient of nucleate boiling in low concentration level of single and hybrid Al2O3-SiO2 water-based nanofluids - M. A. H., Aizzat; Muhamad Zuhairi, Sulaiman; Enoki, K.; Okawa, T. (IOP Publishing, 2019)
Experiments were conducted to identify the Heat Transfer Coefficient (HTC) in saturated pool boiling of single and hybrid water-based nanofluids. In these experiments, Al2O3 and SiO2 nanoparticles were selected and diluted into two separate single nanofluids, and they were mixed in a different ratio from 0:100, 25:75, 50:50, 75:25 and 100:0 percent to achieve a final total concentration of 0.001 vol. %. Successively, the mixtures were used to obtain the HTC values through experimental works. In the present work, it was found that in the lowest concentration (0.00025 vol.%) of Al2O3 nanofluid, the HTC enhanced considerably but deteriorated for SiO2 nanofluid. Separately, as for the hybrid nanofluids, the HTCs were dramatically enhanced at the initial stage but slowly deteriorated once the time variation increased, especially in a higher ratio of SiO2 nanofluid. The deposition of the nanoparticles onto the surface heater suggested being the main factor, where in the present case, the significant coexisting effect of the deposited hybrid nanoparticles (Al2O3 and SiO2) on the heated surface to the changes of ΔT W due to different nanoparticles properties.